The evaluation of the coronary arteries calcification degree by the method of cardiovascular MSCT in patients with vitamin D and homocysteine metabolism disturbance - Nykonenko, O. S.; Nykonenko, A. O.; Chmul, K. O.; Osaulenko, V. V.; Никоненко, Олександр Семенович; Никоненко, Андрій Олександрович; Чмуль, К. О.; Осауленко, В. В.; Никоненко, А. С.; Никоненко, А. А.; Осауленко, Вячеслав Валерійович (Запорізький державний медичний університет, 2020)
In spite of diagnostics and treatment methods development, the ischemic heart disease (IHD) is still the leading cause of disabilities and mortality level in the population. The main reason for IHD pathogenesis is endothelial vascular dysfunction, which further initiates the atherogenesis. The revealing of hyperhomocysteinemia and vitamin D deficiency is determined to increase the risk of the early coronary arteries (CA) atherosclerosis and thrombosis development and to be the prognostic marker of a lethal case. Traditionally, the selective coronary angiography is used to obtain an image of the CAs. However, with the advent of multispiral computed tomography (MSCT), the technique of CT angiography of coronary vessels was introduced, which today has opened wide prospects for determining the degree of coronary calcification and non-invasive evaluation of the anatomy and the degree of CAs narrowing. The aim of the research is to evaluate the degree of CA calcification by the MSCT method in patients with hyperhomocysteinemia and vitamin D deficiency and to determine the correlation between these parameters. Materials and methods. The data of 39 patients who were diagnosed with the CAs pathology by MSCT CAG were analyzed. Results. Patients with high calcium index, greater than 400, with an average cholesterol level of 20.69 ± 2.10 mmol/l, had significantly higher plasma cholesterol levels (P < 0.022 by Mann–Whitney criteria) compared to patients with calcium index less than 400 (mean homocysteine was 13.51 ± 0.97 mmol/l), and greater area of CAs lesions. Conclusions. The MSCT CAG can be used as a screening method to diagnose and clarify the nature of CA lesion. Due to the proven correlation between CI and homocysteine levels, the careful treatment of hyperhomocysteinemia is required both before and after CA surgery Незважаючи на розвиток діагностики та методів лікування, ішемічна хвороба серця (ІХС) залишається провідною причиною інвалідизації та смертності населення. Основна причина ІХС – ендотеліальна судинна дисфункція, що ініціює атерогенез. Показано, що наявність гіпергомоцистеїнемії та дефіциту вітаміну D підвищує ризик раннього розвитку атеросклерозу та тромбозу коронарних артерій і є прогностичним маркером летального наслідку. Традиційно для отримання зображення коронарних артерій використовують селективну коронарну ангіографію. Однак із появою мультиспіральної комп’ютерної томографії (МСКТ) уведена методика КТ-ангіографії коронарних судин, що нині відкрила широкі перспективи визначення ступеня коронарної кальцифікації та неінвазивного оцінювання анатомії та ступеня звуження коронарних артерій. Мета роботи – оцінити ступінь кальцифікації коронарних артерій методом МСКТ у пацієнтів із гіпергомоцистеїнемією та дефіцитом вітаміну D і визначити кореляцію цих параметрів. Матеріали та методи. Вивчили дані 39 пацієнтів, яким діагностували патологію коронарних артерій методом МСКТ КАГ. Результати. Пацієнти з високим кальцієвим індексом (понад 400) і середнім рівнем гомоцистеїну 20,69 ± 2,10 ммоль/л мали вищий рівень гомоцистеїну у плазмі крові (р < 0,022 за критерієм Манна–Уітні) порівняно з пацієнтами з кальцієвим індексом менше ніж 400 (середній показник гомоцистеїну становив 13,51 ± 0,97 ммоль/л) та більшу кількість уражень коронарних артерій. Висновки. МСКТ КАГ можна використовувати як скринінг для діагностики та уточнення характеру ураження коронарних артерій. Зважаючи на доведену кореляцію між рівнями кальцієвого індексу та гомоцистеїну, необхідне ретельне лікування гіпергомоцистеїнемії до і після операції на коронарних артеріях. Несмотря на разработку методов диагностики и лечения, ишемическая болезнь сердца (ИБС) по-прежнему является основной причиной инвалидности и причиной смертности населения. Основная причина развития патогенеза ИБС – эндотелиальная сосудистая дисфункция, которая в инициирует атерогенез. Наличие гипергомоцистеинемии и дефицита витамина D определенно увеличивает риск развития атеросклероза и тромбоза коронарных артерий (CA) и является прогностическим маркером летального исхода. Традиционно селективная коронарная ангиография используется для получения изображения коронарных артерий. Однако с появлением мультиспиральной компьютерной томографии (МСКТ) была введена методика КТ-ангиографии коронарных сосудов, которая открыла широкие перспективы для определения степени коронарной кальцификации и неинвазивной оценки анатомии и степени сужения коронарных артерий. Цель работы – оценить степень кальцификации коронарных артерий методом МСКТ у пациентов с гипергомоцистеинемией и дефицитом витамина D и определить корреляцию этих параметров. Материалы и методы. Изучены данные 39 пациентов, которым диагностирована патология коронарных артерий методом МСКТ КАГ. Результаты. Пациенты с высоким кальциевым индексом (более 400) и средним уровнем гомоцистеина 20,69 ± 2,10 ммоль/л имели значительно более высокие уровни гомоцистеина в плазме (p < 0,022 по критерию Манна–Уитни) по сравнению с пациентами с кальциевым индексом менее 400 (средний показатель гомоцистеина – 13,51 ± 0,97 ммоль/л) и большее количество поражений коронарных артерий. Выводы. МСКТ КАГ можно использовать в качестве скрининга для диагностики и уточнения характера поражений коронарных артерий. Благодаря доказанной корреляции между уровнями кальциевого индекса и гомоцистеина необходимо тщательное лечение гипергомоцистеинемии до и после операции на коронарных артериях.
Оцінювання ступеня кальцинозу коронарних артерій методом МСКТ серця в пацієнтів із порушенням метаболізму вітаміну D і гомоцистеїну
Оценка степени кальциноза коронарных артерий методом МСКТ сердца у пациентов с нарушением метаболизма витамина D и гомоцистеина
Keywords: homocysteine; vitamin D; hyperhomocysteinemia; multispiral computed tomography; coronary calcium index; гомоцистеїн; вітамін D; гіпергомоцистеїнемія; мультиспіральна комп’ютерна томографія; коронарний індекс кальцію; гомоцистеин; витамин D; гипергомоцистеинемия; мультиспиральная компьютерная томография; коронарный кальциевый индекс